Epistatic gene control on the yield of tomato at medium elevation in the tropical agroecosystem - FAJAR PRAKOSO MAWASID; MUHAMAD SYUKUR; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS (Society for Indonesian Biodiversity, 2019)
Abstract. Mawasid FP, Syukur M, Trikoesoemaningtyas. 2019. Epistatic gene control on the yield of tomato at medium elevation in the tropical agroecosystem. Biodiversitas 20: 1880-1886. Cultivation of tomatoes on the middle-low plain generally decreases the quantity and quality of the yield due to high-temperature stress. Increasing the size and weight of lowland tomatoes is needed to enhance national production. Information on the action and genetic model of target characters is needed in the preparation of the assembly program, especially for selection needs. This study aims to obtain genetic information and heritability of tomato yield characters, as a basis for assembling large tomato varieties for the lowlands. The study was conducted using six populations (P1, P2, F1, BCP1, BCP2, and F2) resulting from two different crosses of 99D x Tora (C-I) and 97D x Tora (C-II). The results show that the action of non-additive genes and non-allelic interactions has a large value, with duplicate epistasis being more dominant than complementary epistasis. Duplicate epistasis was found in the character of harvest time, fruit length, fruit diameter, fruit weight in cross I and flowering time, harvest time, fruit length, fruit diameter, and number of fruits in cross II, while complementary epistasis was found in flowering time, fruit weight per plant, number of fruits in cross I, and fruit weight, fruit weight per plant in cross II. Moderate to high heritability was found in the character of fruit length, fruit diameter, fruit weight, and fruit weight per plant. The values are higher in population from the cross I (99D x Tora) for each character, indicating that the cross I has a higher potential for genetic progress than cross II. Selection is recommended when the homozygosity has increased, using the Bulk method or Single Seed Decent. The two methods above can maintain variability in the next generation, so epistasis genes that control target characters are not drastically eliminated.